Rancang mesin peraut lidi kelapa sawit dengan menggunakan motor listrik kapasitas 1800 lidi/jam - Siregar, Zufri Hasrudy; Ramadhan, Andri; Syafputra, Nanda; Mawardi, Mawardi; Refiza, Refiza (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
The palm oil industry is a vital sector in Indonesia, yet it still faces challenges in optimizing waste management, particularly with palm leaf midribs, which are commonly used in various industries. This research aims to design an efficient and economical palm leaf midrib shaving machine with a capacity of 1800 midribs per hour. The novelty of this research lies in the development of a specialized machine for palm leaf midribs, a topic that has not been extensively studied. The research methodology employed is engineering design, involving needs analysis, conceptual design, and implementation using a 0.5 HP electric motor. The materials and tools used include mild steel, stainless steel 304, wood, and other manufacturing components designed for durability and efficiency. The results show that the machine is effective in shaving midribs with a shaft force of 1.91 N and a power output of 0.425 kW, meeting the specified design requirements. In conclusion, this machine can enhance the efficiency of midrib production processes and contribute to more sustainable waste management in the palm oil industry..